Exploring Reflective Journal as a Pathway to Teacher Autonomy: A Qualitative Case Study of EFL Secondary Teachers in Indonesia - Latifa, Intan Septia; Lengkanawati, Nenden Sri; Damayanti, Ika Lestari (Universitas Hamzanwadi, 2025)
Reflective practice and teacher autonomy are conceptually linked but often examined separately. While previous studies have explored reflective practice to enhance individual self-awareness, critical thinking, and teaching competence, little is known about its broader implications for fostering teacher autonomy in institutional and policy contexts. This qualitative case study investigated how reflective teaching journals contribute to the development of professional autonomy among EFL secondary teachers. Specifically, it examined (1) the elements of reflection evident in teachers’ journal entries and (2) how teachers exercise self-initiated pedagogical decision-making in lesson preparation. Five EFL secondary teachers from a senior high school in Serang, Indonesia, were purposively selected. Data comprised 20 reflective journal entries, guided by structured reflection prompts, and semi-structured interviews. Five reflection elements, suggestions, problems, hypotheses, reasoning, and testing were identified using content analysis and thematic coding. Testing and reasoning were most frequently linked to problem-solving strategies for increasing student engagement. Autonomy was evident in teachers’ adaptations of syllabi, sequencing of topics, and supplementation or replacement of textbook materials to meet learners’ needs. The findings indicate that reflective elements do not necessarily occur in a fixed sequence and highlight how reflective journaling can serve as both a diagnostic and developmental tool for teacher autonomy. The study recommends greater institutional support for diverse reflective practices to strengthen teachers’ capacity for informed, context-responsive decision-making in EFL classrooms.